2012
DOI: 10.1159/000342703
|View full text |Cite
|
Sign up to set email alerts
|

A Thickened Formula Does Not Reduce Apneas Related to Gastroesophageal Reflux in Preterm Infants

Abstract: Background: Apnea of prematurity (AOP) occurs frequently in preterm infants and a variable proportion of AOP can be induced by gastroesophageal reflux (GER). Conservative treatment, including dietary modifications, should be the first-line approach for both GER and GER-related apneas in this population. Objectives: To evaluate the efficacy of a starch-thickened preterm formula (PF) in reducing the frequency of apneas related to GER. Methods: Preterm infants with AOP were studied by combined impedance and pH mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
1
16
0
2
Order By: Relevance
“…Moreover, as we have subsequently shown [30], the number of apneas is significantly higher after nonacid GER episodes, which prevail in the early postprandial period [31], confirming Wenzl's previous findings [32]. In accordance with these results, neither thickened formulas [33] nor the administration of sodium alginate [34] was found to improve the rate of apneas in symptomatic preterm infants. Eventually, a significant temporal association between cardiorespiratory events and GER, particularly remarkable among obstructive apneas and MII-GER, has been recently reported by Nunez et al [35] in a small cohort of both term and preterm infants.…”
Section: Gastroesophageal Reflux: Clinical Presentationsupporting
confidence: 83%
“…Moreover, as we have subsequently shown [30], the number of apneas is significantly higher after nonacid GER episodes, which prevail in the early postprandial period [31], confirming Wenzl's previous findings [32]. In accordance with these results, neither thickened formulas [33] nor the administration of sodium alginate [34] was found to improve the rate of apneas in symptomatic preterm infants. Eventually, a significant temporal association between cardiorespiratory events and GER, particularly remarkable among obstructive apneas and MII-GER, has been recently reported by Nunez et al [35] in a small cohort of both term and preterm infants.…”
Section: Gastroesophageal Reflux: Clinical Presentationsupporting
confidence: 83%
“…There were, however, no significant differences in the frequency of apnoeas in the epochs either preceding or following a reflux event (but only 6 preterm infants were investigated). Another study, suggesting that GOR does not cause apnoea, concerned the lack of effectiveness of feed-thickening in reducing apnoeas [24]. Twenty-four infants with apnoea of prematurity underwent oesophageal pH, MII, and cardiorespiratory monitoring after alternating formula thickened with amylopectin with unmodified formula.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four infants with apnoea of prematurity underwent oesophageal pH, MII, and cardiorespiratory monitoring after alternating formula thickened with amylopectin with unmodified formula. The feed thickener was effective in significantly reducing the oesophageal acid exposure, but there was no significant difference in the frequency of clinically relevant apnoea [24]. Indeed, an editorial on the above paper suggested that apnoea of prematurity should not be treated with anti-reflux medications unless clear data proves a causal relationship [25].…”
Section: Discussionmentioning
confidence: 99%
“…32 Also, thickened formulas do not seem to reduce acid or nonacid gastroesophageal reflux in preterm infants more than non-thickened formulas. 33 …”
Section: Gastroesophageal Reflux and Apneamentioning
confidence: 99%